Haversine Formula to Find The Nearest PetShop - Rakhmat Purnomo; Tri Dharma Putra; Hadi Kusmara; Wowon Priatna; Fajar Mukharom (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The population of cats and dogs is increasing, whether they are kept or not. The public's awareness to raise these animals needs to be supported by a business place for keeping and buying and selling pet food or a PetShop. People who keep animals often have difficulty (1) finding the nearest PetShop, (2) access to the location, (3) knowing what services are provided, even (4) knowing whether there is a willingness to consult animal care and make a consultation appointment. This study aims to bring together PetShop and the community in the care and maintenance of animals, especially cats and dogs in Bekasi City. The system development life cycle method used is WaterFall. The WaterFall method consists of 5 stages, namely: Communication, Planning, Modeling, Construction, and Deployment. On stage Contruction, the Haversine Formula is inserted to find the nearest PetShop and with the help of the Google Maps API, a route to the PetShop is determined from the application user. Unified Modeling language (UML) diagrams are used during the analysis and system design processes such as Use Case Diagrams, Activity Diagrams, Sequence Diagrams, Class Diagrams, Data Models, and User Interfaces. The result of this research is the ZuPet Web application which was built according to the Waterfall system development methodology, and the Haversine Formula has been inserted to optimize the search for the shortest route. The functionality of the application has been tested using the BlackBox Testing method. The application can be accessed at the address https://zupet.my.id.